Within and between day repeatability of the incremental shuttle walking test in patients with thoracic cancer. (July 2018) - Wilcock, Andrew; Koon, Sim; Manderson, Cathann; Taylor, Vicky; Maddocks, Matthew
Abstract: Background: Breathlessness is common in patients with thoracic cancer but difficult to manage. The Incremental Shuttle Walking Test (ISWT) can help assess new treatments, but its repeatability has not been described in this group. Aim: To examine within and between day repeatability of the ISWT in this setting. Methods: Patients with incurable thoracic cancer were recruited from outpatient clinics at a University Hospital. Two ISWTs were completed one hour apart on two consecutive days, with the first test for familiarization purposes only. Repeatability of distance walked was examined using Bland and Altman plots and assessed as the single determination (within subject) standard deviation of the difference between tests and its 95% range. Results: Forty-one patients participated and completed all tests. Mean (SD) distance walked was 333 (134), 349 (129) and 353 (130) m over the three tests, with the mean difference significantly different from zero between days (16 m, 95% CI 8–24 m, P = 0.043) but not within days (5 m, 95% CI –2 to 12 m, P = 0.47). Within and between day single determination SD and 95% ranges were 30 (−31 to 91) m and 36 (−37 to 109) m respectively. Conclusions: These data help inform the design of studies making use of the ISWT and the interpretation of their findings. Highlights: The Incremental Shuttle Walking Test is a popular assessment of exercise capacity. We formally describe its repeatability in patients with thoracic cancer. These data inform intervention effect interpretation and sample size calculations.